From Mimesis To Imaging The representation of art as a critical visual-resource Considerations and emblematic cases - Scalise, Adriana (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
The purpose of this contribution consists in looking at that particular photography sector which is related to the photographic representation of art. It intends to investigate the characteristics of this kind of photography and to search out that probable expressive originality which springs from the tension between the imitative ability and the creative will. Starting from the etymology of the word "mimesis" considered in its double meaning of "imitation" and of "image". I tried to outline the activity relied to the photographic representation of art, in the attempt to catch out, through the historical evolution, its aesthetic value